ANALISIS NILAI MORAL DALAM LEGENDA BUKIT PERAK KARYA RICKY A. MANIK - Abdoel Gafar; Elsa Utari (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research was motivated by finding moral values in the legend of Bukit Perak by Ricky A. Manik. This study aims to describe the moral values contained in the legend of Bukit Perak by Ricky A. Manik. This research uses a qualitative type of descriptive research. The data of this research is in the form of findings related to 7 aspects of moral values including; care for others, help each other, be deliberative, live in harmony, keeping promises, forgiving, respecting others contained in the legend. The findings are analyzed based on the existing theory in the literature study which the author uses as a theoretical basis in analyzing this research. The qualitative descriptive research is used as a way to descript the moral values contained in this legend. The results of this study can be described by the author that the legend of Bukit Perak by Ricky A. Manik contains moral values from the aspect of moral values including; care for others, help each other, be deliberative, live in harmony, make promises, forgiving, respecting for others. The number of findings used as data in the form of citations about moral values was 83 citations. From the results of the research, it is suggested that the legend of Bukit Perak as a Jambi regional literature with requirements with moral values can be used as a development of learning materials for local content in schools.